2009
DOI: 10.1007/s00464-009-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic single-site surgery for placement of an adjustable gastric band: initial experience

Abstract: In our experience, LESS surgery for adjustable gastric banding shows this technique to be both feasible and safe for selected patients. Although technical limitations exist that will be improved upon, further studies are needed to compare LESS surgery for placement of an adjustable gastric band with traditional laparoscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…The most important merit of RPS is cosmesis [3,4,6,9,11,13]. Therefore, this cosmetic merit must be retained as long as possible when performing RPS for total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important merit of RPS is cosmesis [3,4,6,9,11,13]. Therefore, this cosmetic merit must be retained as long as possible when performing RPS for total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, reduced port surgery (RPS), including single port surgery (SPS), in which fewer ports are used than in conventional procedures, has become increasingly popular in various surgical fields [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There have been reports describing the application of RPS to laparoscopic sleeve gastrectomy for morbid obesity or laparoscopic partial gastrectomy for gastrointestinal stromal tumors, and the use of RPS has recently also been reported in laparoscopy-assisted distal gastrectomy for gastric cancer [1,7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One, by Teixeira et al [7], was excluded from the analysis as the presented data on 10 patients was further included by the authors in larger published case series [8]. Seven articles were case reports or series of cases of laparoscopic adjustable gastric banding (LAGB) using one of the SILS techniques (a total of 87 patients) [8][9][10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…As most of the studies were 'feasibility studies' they did not formally assess postoperative pain. Nevertheless, one study reported decreased opioid analgesics use in the postoperative period [7]. Kim et al …”
Section: Discussionmentioning
confidence: 99%
“…Simpler procedures for bariatric surgery, such as adjustable gastric banding, have been described recently [27] , and single access was suggested for more advanced bariatric techniques, including sleeve gastrectomy and gastric bypass. Conventional laparoscopic Roux -en -Y gastric bypass (LRYGB) is the gold standard for bariatric surgery.…”
Section: Cambridge Endo Instrumentsmentioning
confidence: 99%